Association between growth differentiation factor 15 levels and gestational diabetes mellitus: A combined analysis - Lu, Yi-Cheng; Liu, Song-Liang; Zhang, Yu-Shan; Liang, Fei; Zhu, Xiao-Yan; Xiao, Yue; Wang, Jing; Ding, Cong; Banerjee, Sudipta; Yin, Jie-Yun; Ma, Qiu-Ping (Frontiers in Endocrinology, 2023)
Objective: Gestational diabetes mellitus (GDM) is a common glucose metabolism disease occurs in pregnancy that affects both maternal and neonatal health. Recently, increasing studies have attached importance to the relationship between growth differentiation factor 15 (GDF-15) and GDM, but the results were inconclusive. Therefore, we conducted a meta-analysis to examine the association between GDF-15 and GDM. Materials and methods: A systematical search was performed in Gene Expression Omnibus (GEO), PubMed and Google Scholar till Oct 27, 2022. We first calculated the mean and standard deviation of GDF-15 expression levels from the included eligible datasets and articles. Then, a meta-analysis was conducted to depict the difference in GDF-15 mRNA or GDF-15 protein expression between case and control groups by using conservative random effect model. Moreover, the potential publication bias was checked with the aid of Begg’s test and Egger’s test. Finally, sensitivity analyses were performed by changing the inclusion criteria. Results: In summary, 12 GEO datasets and 5 articles were enrolled in our study, including 789 GDM patients and 1202 non-GDM pregnant women. It was found that the expression levels of GDF-15 mRNA and GDF-15 protein in late pregnancy were significantly higher in GDM patients compared with non-GDM pregnant women, with the standard mean difference (SMD) and 95% confidence interval (95% CI) of 0.48 (0.14, 0.83) and 0.82 (0.32-1.33), respectively. Meanwhile, a slightly weakened associations between GDF-15 protein levels and GDM were also observed in the middle pregnancy, with SMD (95% CI) of 0.53 (0.04-1.02). Conclusion: In all, our results suggested that the expression levels of GDF-15 were significantly higher in GDM patients compared with non-GDM pregnant women, especially in the late pregnancy.